2019
DOI: 10.1186/s13068-019-1550-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and manipulation of Neurospora crassa genes involved in sensitivity to furfural

Abstract: Background Biofuels derived from lignocellulosic biomass are a viable alternative to fossil fuels required for transportation. Following plant biomass pretreatment, the furan derivative furfural is present at concentrations which are inhibitory to yeasts. Detoxification of furfural is thus important for efficient fermentation. Here, we searched for new genetic attributes in the fungus Neurospora crassa that may be linked to furfural tolerance. The fact that furfural is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Expression of 22 orphan genes required that at least one type of carbon resource was present in the media, while expression of 56 other orphan genes was only detected in the absence of carbon. Revisiting expression data collected from experiments investigating N. crassa ’s tolerance to furfural (Feldman et al 2019) identified that 245, 239, 257, and 232 orphan genes exhibited measurable levels of expression in the wild-type condition, DMSO (the carbon blank control), furfural, and HMF treatments ( Tables S7, S8 ). Within the 291 genes expressed in either furfural or HMF cultures or both, 61 were not expressed in the wild-type condition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of 22 orphan genes required that at least one type of carbon resource was present in the media, while expression of 56 other orphan genes was only detected in the absence of carbon. Revisiting expression data collected from experiments investigating N. crassa ’s tolerance to furfural (Feldman et al 2019) identified that 245, 239, 257, and 232 orphan genes exhibited measurable levels of expression in the wild-type condition, DMSO (the carbon blank control), furfural, and HMF treatments ( Tables S7, S8 ). Within the 291 genes expressed in either furfural or HMF cultures or both, 61 were not expressed in the wild-type condition.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, many more het-like genes (46 vs. 15) were significantly up-regulated (P < 0.05) on MSM than on BM during that first branching stage. (Wang et al 2014;Wang, Miguel-Rojas, et al 2019) on media with various carbon resources (Wang et al 2015;Feldman et al 2019). 342 orphan genes were expressed at measurable levels in at least two stages in each of the three developmental processes (Tables S6-S7), including eight stages of sexual development on SCM (salmon pink, totaling 484 orphan genes with measurable expression), four stages of asexual growth on BM (beige, totaling 457 orphan genes with measurable expression) and four stages of asexua-sexual growth on MSM (light blue, totaling 489 orphan genes with measurable expression).…”
Section: Expression Dynamics Of Orphan and Het-like Genes In Response...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pyronema may simply exist as dormant ascospores or sclerotia that require the heat and/or chemical changes associated with fire to break dormancy and initiate germination ( Emerson, 1947 ; El-Abyad and Webster, 1968a ). For example, plant-derived polysaccharides such as hemicellulose burned at high temperatures result in the formation of furfural, which triggers germination of N. crassa ascospores ( Eilers and Sussman, 1970 ; Feldman et al, 2019 ). One recent hypothesis suggests that pyrophilous fungi may live as endophytes for the majority of their life history, abandoning their plant hosts after they are killed by fire ( Raudabaugh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%